2022
DOI: 10.22159/ajpcr.2022.v15i8.45065
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sutureless, Glue-Less Conjunctival Autograft Versus Sutured Limbal Conjunctival Autograft for Primary Pterygium

Abstract: Objectives: The objective of the study was to compare and evaluate efficacy of two surgical techniques for the management of primary pterygium in terms of complications and post-operative signs and symptoms. Methods: The study included 60 patients with primary pterygium. The mean age was 42±10 years (range 22–62 years). Simple excision under local anesthesia was performed followed by closure of the bare sclera by suture less and glue free conjunctival autograft in 30 patients (Group I), versus the conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…All the included studies showed a low risk of performance bias apart from Elwan 16. Four articles showed a low risk of detection bias,13 16 22 23 and all the included articles showed a low risk of attribution bias. All the included articles showed a low risk of reporting bias, and eight articles showed unclear risk of other sources of bias (figure 2).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…All the included studies showed a low risk of performance bias apart from Elwan 16. Four articles showed a low risk of detection bias,13 16 22 23 and all the included articles showed a low risk of attribution bias. All the included articles showed a low risk of reporting bias, and eight articles showed unclear risk of other sources of bias (figure 2).…”
Section: Resultsmentioning
confidence: 91%
“…After evaluating titles and abstracts, 22 articles were excluded, resulting in 13 articles that underwent full-text assessment. Ultimately, 11 RCTs met the eligibility criteria 13–23…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations